Rendezvous with rama ebook - Clarke, Arthur C. (Rama, 2012)
Astronauts explore an alien spacecraft hurtling toward the sun in this Hugo and Nebula Award–winning novel—“a stone-cold classic” of hard sci-fi ( The Guardian ).   An enormous cylindrical object has entered Earth’s solar system on a collision course with the sun. A team of astronauts are sent to explore the mysterious craft, which the denizens of the solar system name  Rama . What they find is astonishing evidence of a civilization far more advanced than ours. They find an interior stretching over fifty kilometers; a forbidding cylindrical sea; mysterious and inaccessible buildings; and strange machine-animal hybrids, or “biots,” that inhabit the ship. But what they don’t find is an alien presence. So who—and where—are the Ramans?   Often listed as one of Clarke’s finest novels,  Rendezvous with Rama  won numerous awards, including the Hugo, the Nebula, the Jupiter, and the British Science Fiction Awards. A fast-paced and compelling story of an enigmatic encounter with alien technology,  Rendezvous with Rama  offers both answers and unsolved mysteries that will continue to fascinate readers for generations.   “Mr. Clarke is splendid . . . We experience that chilling touch of the alien, the not-quite-knowable, that distinguishes SF at its most technically imaginative.” — The New York Times